sj-docx-1-trr-10.1177_03611981211004127 – Supplemental material for Evaluating Pedestrian Crash-Prone Locations to Formulate Policy Interventions for Improved Safety and Walkability at Sidewalks and Crosswalks - Mallikarjun Patil (10523666); Bandhan Bandhu Majumdar (10523669); Prasanta K. Sahu (10523672) (2021)
Supplemental material, sj-docx-1-trr-10.1177_03611981211004127 for Evaluating Pedestrian Crash-Prone Locations to Formulate Policy Interventions for Improved Safety and Walkability at Sidewalks and Crosswalks by Mallikarjun Patil, Bandhan Bandhu Majumdar and Prasanta K. Sahu in Transportation Research Record